INDEKS GLIKEMIK NUGET TEMPE SAWI PECAY - Ertriani Anindya Meiflorisa; Tejasari Tejasari; Giyarto Giyarto (JURNAL AGROTEKNOLOGI, 2017)
Nowadays, healthy food with low glycemic index is very usefull to people with diabetes mellitus because it will not increase blood sugar levels quickly. The purpose of this study was to know the glycemic index values of nugget made from tempeh and pecay, and evaluate macro nutrient density of the nugget. In this research used glycemic index (GI) test for subject with healthy criteria. Each formula consisted of nugget from tempeh and pecay, P1 (40% tempeh : 30% pecay : 25% flour : 5% tapioca), P2 (45% tempeh : 25% pecay : 25% flour : 5% tapioca), P3 (50% tempeh : 20% pecay : 25% flour : 5% tapioca), P4 (55% tempeh : 15% pecay : 25% flour : 5% tapioca), P5 (60% tempeh : 10% pecay : 25% flour : 5% tapioca) and P6 (65% tempeh : 5% pecay : 25% flour : 5% tapioca). The best formula is the nugget made with from 55% tempeh : 15% pecay. That formula has value of glicemic index were 22%, moisture content were 50%, ash content were 2,4%, fat content were 19%, protein content were 54,6%, carbohydrates content were 24%. The dietary fiber as Insoluble Dietary Fiber were 22,46%, Soluble Dietary Fiber were 2,26% and Total Dietary Fiber were 24,72%. Keywords: nugget, tempeh, pecay, glycemic index